Saturday

April 18, 2015

April 18, 2015

Posted by **FEBIN** on Monday, January 16, 2012 at 7:19pm.

- arithmetic -
**Reiny**, Monday, January 16, 2012 at 11:11pmsum of n terms of 1st = (n/2)(10 + 36(n-1))

= (n/2)(36n - 26)

sum of 2n terms of 2nd = (2n/2)(72 + 5(2n-1))

= n(10n + 67)

(n/2)(36n - 26) = n(10n + 67)

divide by n, and multiply by 2

36n - 26 = 20n + 134

16n = 160

n = 10

check:

sum(10 for 1st) = 5(10 + 36(9)) = 1670

sum(20 for 2nd) = 10(72 + 19(5)) = 1670

all is good!

**Answer this Question**

**Related Questions**

arithmetic - 1. The first and last term of an A.P are, a and l respectively, ...

arithmetic - 1. The first and last term of an A.P are, a and l respectively, ...

math - Find the sum of the first 60 terms of the arithmetic sequence whose ...

arithmetic - find the common difference of A.P whose first term is 5 and the sum...

maths - 1) The first term of arithmetic progression is -20 and the sum of it's ...

Precalculus - The 8th term in an arithmetic sequence is 5, and the sum of the ...

math - in an arithmetic sequence the common difference is equal to 2.the first ...

Maths - 1..The first 2 terms of a geometric progression are the same as the ...

Math - 1) If the sum of the first n terms of a series is Sn where Sn=2nē-n, (a)...

math - 1) If the sum of the first n terms of a series is Sn where Sn=2nē-n, (a)...